2023
DOI: 10.2340/jrm.v55.2572
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Prolotherapy for Osteoarthritis: A Systematic Review

Abstract: Objective: Current treatments for osteoarthritis do not resolve the underlying cause. Dextrose prolotherapy is an alternative method that has been proposed for treatment of osteoarthritis, due to its ability to aid tissue regeneration, improve clinical manifestations, and repair damaged tissue structures, which are pathological conditions in osteoarthritis. The aim of this systematic review was to evaluate the efficacy of dextrose prolotherapy compared with other interventions in the management of osteoarthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study conducted a comprehensive systematic review and meta‐analysis on the impact of prolotherapy in patients with KOA. While the precise mechanisms of prolotherapy on soft tissues and joints are not fully understood, previous research has proposed several potential mechanisms 22,24,36,45,46 . One mechanism is the reduction of local inflammation, where the injection of a proliferative solution may aid in decreasing inflammation and promoting healing, potentially alleviating symptoms like pain and stiffness in KOA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted a comprehensive systematic review and meta‐analysis on the impact of prolotherapy in patients with KOA. While the precise mechanisms of prolotherapy on soft tissues and joints are not fully understood, previous research has proposed several potential mechanisms 22,24,36,45,46 . One mechanism is the reduction of local inflammation, where the injection of a proliferative solution may aid in decreasing inflammation and promoting healing, potentially alleviating symptoms like pain and stiffness in KOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive review of literature on prolotherapy highlights its potential benefits in managing OA symptoms, particularly in the knee joint. Despite the lack of homogeneity in studies, recent trials have demonstrated that dextrose prolotherapy can effectively reduce pain scores and improve stiffness, function, and quality of life in patients with KOA 20–25 . Dextrose, a cost‐effective and readily available substance, has gained prominence as an injection‐based therapeutic option for managing chronic painful musculoskeletal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, treatment options for osteoarthritis primarily focus on managing symptoms and slowing disease progression [ 64 , 65 ]. Despite the widespread use of certain medications like glucosamine and cortisone, their efficacy in significantly regenerating damaged articular cartilage remains limited [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hasarlı olan tendon, ligament, kıkırdak dokularının tedavisinde kullanılır (Örsçelik & Solmaz, 2023). Proloterapinin etki mekanizması net olarak anlaşılamamış olsa da etkisini rejeneratif süreci aktive ederek gösterdiği düşünülmektedir (Waluyo, Artika, Insani Nanda, Gunawan, & Zainal, 2023).…”
Section: Introductionunclassified
“…Ancak uygulama sonrası uygulama alanındaki hücreler ortamda meydana gelen lokal inflamatuar yanıt sonrasında salınan TGF-beta, epidermal büyüme faktörü, insülin benzeri büyüme faktörü, fibroblast büyüme faktörü gibi çeşitli büyüme faktörleri salgılayarak fibroblastları aktive edip kollajen üretimini tetiklemektedir (Waluyo et al, 2023). Meydana gelen bu rejeneratif inflamatuar yanıt ile hasarlı dokudaki ağrı, ligament laksasyonu ve laksasyondaki azalmaya bağlı olarak eklem instabilitesi azalmaktadır (Dagenais, Yelland, Del Mar, & Schoene, 2007;Waluyo et al, 2023). Bu tedavi yönteminde temel prosedür proliferan solüsyonun hassas ligaman ve tendinöz yapılara ve bitişik eklem boşluklarına enjekte edilmesi esasına dayanır.…”
Section: Introductionunclassified